Cats’ welfare and the relationship with their tutors during quarantine caused by COVID-19 in Brazil - Aptekmann, Karina Preising; Oliveira, Leticia Leal; Barioni, Graziela (Archives of Veterinary Science, 2023)
This study aimed to identify behavioral changes or welfare impairments in cats in response to home isolation due to the COVID-19 pandemic in Brazil, as well as the emotional role these animals may play with their tutors. Online questionnaires were answered by 419 cat’s tutors in Brazil, who reported changes in the household routine because of the COVID-19 pandemic. The questions addressed information about the cat in the household, the tutor-cat relationship, the cat behavior, the house environment, and the changes occurred in the face of social isolation. It was evident that changes in people's routines were frequent and staying longer at home was the change most reported by the participants. Thus, cats were left alone for less time compared to the period before the quarantine. This led to an increase in the amount of time that tutors spent playing or paying attention to their cats. The quarantine period generated minimal undesirable behavioral changes in the cats, and the fact that the tutors stayed home longer contributed to reducing these changes. The fact that a cat could become infected by the new corona virus SARS-CoV-2 was known by less than half of the interviewees, which did not influence any tutor to think of getting rid of their cat. We highlight that the fact that the tutors stayed longer at home, interacting with their cat, contributed to reduce the undesirable behavioral changes in the cats. This also improved the tutors' perception of the cats' needs and behaviors, also reflecting on a greater perception of happiness in cats.